The Implementation of Story-Telling Learning Models to Improve Students’ Public Speaking Skill in Social Studies Lessons at SMPN 1 Peusangan - Agustina, Yenni; Zahara, Zahara; Chairani, Mira; Suriyanto, Suriyato (International Conference on Multidisciplinary Research, 2020)
The method used in this research is Classroom Action Research. Difficulties experienced by some students in learning social studies can be listed as difficulties in understanding lessons, inadequateconcentration in studying, insufficient encouragement, lack of sense of need in learning, difficulties inremembering subject materials, insufficient student’s attention in learning activities, absence of the useof storytelling model learning to improve public speaking, and the low learning outcomes in socialstudies subjects. The storytelling learning model is believed to be able to improve student’s publicspeaking ability. The subjects in this study were students of class IX in the 2019/2020 school year atSMPN 1 Peusangan. Based on the results, it can be seen that there is an increase in the students' publicspeaking ability after the implementation of the story-telling learning model. The results show that theaverage value of individual mastery increased from cycle I to cycle II. In the first cycle, the averageindividual mastery value is 73% (16 students), while 27% (6 students) did not reach mastery levelrequirement. In the second cycle, there was an increase in individual mastery; all of 22 students reachedthe mastery level requirement. Based on the increase in individual and classical mastery values, theapplication of the story-telling learning model contributes to improve student’s public speaking ability.Since the mastery values are 90%, the study was only carried out until the second cycle. Based on theresults, it can be concluded that there were positive changes which were marked by the presence ofmany students who were happy and interested in following the story-telling strategy. The percentage ofstudents' positive responses to public speaking was 95,46 %. Meanwhile, the average negative responseof students was 4.54%. This shows that the story-telling learning model is in demand by students.Keywords: Public Speaking, Storytelling Learning Model